2009
DOI: 10.4161/cam.3.3.8399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-cadherin overexpression on the adhesion properties of embryonic stem cells

Abstract: Constitutive overexpression of N-cadherin in mouse embryonic stem cells led to marked changes in the phenotype and adhesion properties of these cells. The changes included the formation of smaller embryonic bodies, elevated mRNA and total protein levels of N-cadherin, and increased amounts of p120 catenin and connexin-43. N-cadherin cells exhibited decreased attachment to non-cell surfaces, while their adhesiveness to each other and to rat neonatal cardiomyocytes was significantly elevated. The findings sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Therefore, the exact role of Cx43 in metastasis is still to be investigated more in detail than ever. In terms of relationships between connexins and cell adhesion molecules, accumulating evidence indicated that cell adhesion molecules have been implicated in connexins docking, as L-CAM [24], E-cadherin [25], and N-cadherin [26] activities appear to be important for GJIC. In addition, the cadherin repertoire can determine the type of GJIC.…”
Section: Cx43 In Mlnmentioning
confidence: 98%
“…Therefore, the exact role of Cx43 in metastasis is still to be investigated more in detail than ever. In terms of relationships between connexins and cell adhesion molecules, accumulating evidence indicated that cell adhesion molecules have been implicated in connexins docking, as L-CAM [24], E-cadherin [25], and N-cadherin [26] activities appear to be important for GJIC. In addition, the cadherin repertoire can determine the type of GJIC.…”
Section: Cx43 In Mlnmentioning
confidence: 98%
“…hiPSC- and hESC-CMs were, however, connected by 'primitive ICDs’ [ 58 ], which may contribute to the immature electrical properties of these cells. Unlike Cx43, over-expression of N-cadherin [ 80 ] in mESCs does not interfere with the formation of functional CMs. In fact, mESC-CMs that over-express N-cadherin show increased levels of Cx43 [ 80 ], supporting the idea that adherens junction formation drives connexin expression [ 81 ].…”
Section: State Of Hpsc-cms During Differentiationmentioning
confidence: 99%
“…28 Amplification using the mtDNA primers was done with 0.25 ng of total DNA. A standard curve (5, 1, 0.5, 0.05, and 0.005 ng of total DNA/reaction) was performed with the 18S primers.…”
Section: Dna Isolationmentioning
confidence: 99%